Alocação de recursos para redes LTE (Long Term Evolution) em bandas não-licenciadas - Lima, Henrique Valle de (2018)
LTE (Long Term Evolution) in unlicensed band (LTE-U) has emerged as a promising solution to the problem of the huge growth in mobile data traffic. It expands the benefits of LTE with bands of the unlicensed 5 GHz spectrum, mainly used in IEEE 802.11. But uncertainties as to the availability of these bands make the adoption of LTE-U a great challenge. In this dissertation, we propose a mixed linear programming approach for allocating resources in order to expand service by LTE-U. Subsequently, we propose a stochastic programming approach, taking into account the randomness of the unlicensed band, allocating resources under a certain control in the risk of conflict with IEEE-802.11. We used three models of the literature for the demand for IEEE 802.11 in our tests. The results highlight the importance of prior knowledge about the distribution of this demand.